2020
DOI: 10.3390/nu12020425
|View full text |Cite
|
Sign up to set email alerts
|

Whey Peptides Stimulate Differentiation and Lipid Metabolism in Adipocytes and Ameliorate Lipotoxicity-Induced Insulin Resistance in Muscle Cells

Abstract: Deregulation of lipid metabolism and insulin function in muscle and adipose tissue are hallmarks of systemic insulin resistance, which can progress to type 2 diabetes. While previous studies suggested that milk proteins influence systemic glucose homeostasis and insulin function, it remains unclear whether bioactive peptides generated from whey alter lipid metabolism and its accumulation in muscle and adipose tissue. Therefore, we incubated murine 3T3-L1 preadipocytes and C2C12 myotubes with a whey peptide mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Enriched whey protein fractions inhibit adipogenesis of 3T3-L1 ( Rajic et al, 2010 ). More recently, D’Souza et al (2020) demonstrated that whey protein hydrolyzed by pepsin and pancreatin enhances 3T3-L1 adipocyte differentiation and triacylglycerol accumulation. However, it has not yet been reported that bioconversion of whey exerts an anti-adipogenic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Enriched whey protein fractions inhibit adipogenesis of 3T3-L1 ( Rajic et al, 2010 ). More recently, D’Souza et al (2020) demonstrated that whey protein hydrolyzed by pepsin and pancreatin enhances 3T3-L1 adipocyte differentiation and triacylglycerol accumulation. However, it has not yet been reported that bioconversion of whey exerts an anti-adipogenic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the addition of leucine to evogliptin treatment in high‐fat‐fed mice has also been shown to improve glucose tolerance (an effect not observed in evogliptin‐only group) 36 . In vitro, C2C12 myotubes treated with hydrolysed whey protein isolate showed restoration of palmitate‐suppression of pAkt signaling and GLUT4 expression 37 . Moreover, treatment with an isoleucine‐leucine dipeptide previously improved glucose uptake in L6 myotubes 38 .…”
Section: Discussionmentioning
confidence: 98%
“…Animal and cell culture models suggest WP may promote fat metabolism by influencing both adipose and muscle ( 43 , 44 ). WP has been shown to impact adipose tissue by upregulating signaling pathways associated with the breakdown of triglycerides into FFA ( 43 , 44 ), fat oxidation ( 45 ), thermogenesis ( 43 ), and antagonists to fatty acid synthesis ( 44 ). Conversely, in myotubes, WP has been shown to upregulate signaling pathways related to free fatty acid transport to mitochondria ( 43 ) and mitochondrial ability to oxidize free fatty acids ( 44 ).…”
Section: Discussionmentioning
confidence: 99%